Providing Home-Based Support for Children with Chronic Conditions in an Urban Slum: Experiences from a Community-Based Palliative Care Program in Bangladesh. (March 2021) - Chowdhury, Mostofa Kamal; Shopna, Khadija; Lynch-Godrei, Anisha; Jain, Mehr; Farheen, Nadia; Begum, Noorjahan; Ahmad, Nezamuddin; Doherty, Megan
We describe the palliative care needs of children with chronic conditions and their caregivers in an urban slum in Bangladesh. In this cross-sectional study, we interviewed 25 caregivers whose children receive support from a community-based program lead by community health workers, that provides medication, medical supplies, food, caregiver training, and psychological support free of charge. The chronic conditions of children in the program included cerebral palsy (80%), congenital heart disease (8%), neurodegenerative conditions (4%), cancer (4%), and intellectual disabilities (4%). Common symptoms included cough or breathing problems (64%), fever (56%), and pain (56%). Most caregivers (96%) reported they were unable to do any paid work due to their child's needs and in all families, the child's condition had a significant impact on their financial situation. Community-based palliative care programs can be developed to support children with chronic conditions who may not access care from acute care facilities.